2021
DOI: 10.1002/nop2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s experiences of support when fearful during treatment for acute lymphoblastic leukaemia—A longitudinal interview study

Abstract: Fear is common in sick children who interact with the healthcare system, and children with acute lymphoblastic leukaemia (ALL) are no exception. Perhaps their fear is unavoidable, yet all children have the right to adequate support in managing their situation.Such support can be especially important during a long, unpleasant course of treatment. This study focuses on the types of support from healthcare professionals and parents that 5-to-9-year-old children with ALL report as helping them when they feel scare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Leibring and Anderzén-Carlsson 23 reported that children found restraint supportive when they were fearful in relation to their cancer treatment. Circumstances always influence how we experience a situation, and the fact that several participants in this study experienced fear related to medical procedures might have colored their experiences.…”
Section: M Itati O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…Leibring and Anderzén-Carlsson 23 reported that children found restraint supportive when they were fearful in relation to their cancer treatment. Circumstances always influence how we experience a situation, and the fact that several participants in this study experienced fear related to medical procedures might have colored their experiences.…”
Section: M Itati O N Smentioning
confidence: 99%
“…Karlsson et al 22 summarized that restraint assigns the child a passive role and causes panic, loss of control, and feelings of powerlessness. However, a recent study of children aged 5–9 years diagnosed with cancer offered an opposite perspective, as some of the children explained that they found it supportive to be physically or verbally forced to comply with certain procedures 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalization for pre-schoolers is very stressful and potentially traumatising due to the hazardous new environment and medical procedures that can trigger anxiety, rage, powerlessness, and a loss of control (Godino-Iáez et al, 2020;Islaeli et al, 2020). The child is unable to do his routine activities Nurse Key (2020), and the worst scenario is when the children watch strangers in white uniforms in an unfamiliar environment (Kleye et al, 2021) and are afraid of needles and syringes (Leibring & Anderzén-Carlsson, 2022). A preschooler also experiences fears at a child's developmental stage, such as fear of darkness (Csonka, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Aggression, trouble sleeping or eating, or fear can be expressed through children's facial expressions and gestures and physiological changes in their bodies (Salmela, Aronen, & Salanterä, 2011). However, the response is highly individualised and dependent on the child's developmental age, previous illness history, and coping skills in the hospital (Kleye et al, 2021;Leibring & Anderzén-Carlsson, 2022).…”
Section: Introductionmentioning
confidence: 99%